2020
DOI: 10.51302/tce.2020.485
|View full text |Cite
|
Sign up to set email alerts
|

Análisis documental: importancia de los entornos virtuales en los procesos educativos en el nivel superior

Abstract: El presente estudio tuvo como propósito conocer la importancia de los entornos virtuales en los procesos educativos en el nivel superior. Se llevó a cabo una revisión sistemática de la literatura de 22 trabajos científicos publicados entre 2011 y 2019 en diferentes países de América Latina y Europa. Los resultados son los siguientes: el concepto de «entornos virtuales» se asocia a un software o a una aplicación informática, espacio o medio en la red que facilita la comunicación. Sus características son la cola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
3
0
5
Order By: Relevance
“…The activities that were modified, as expected, were learning activities and evaluation [28], along with an increase in the number of advising/tutorship hours, given that didactic strategies and the manner in which interaction and evaluation remotely had to be modified. Providing the students with more time for advising/tutorship, as pointed out by [20], promotes active interaction and participation of students, providing evidence of the role as a companion that the professor must play in education mediated by the ICT.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The activities that were modified, as expected, were learning activities and evaluation [28], along with an increase in the number of advising/tutorship hours, given that didactic strategies and the manner in which interaction and evaluation remotely had to be modified. Providing the students with more time for advising/tutorship, as pointed out by [20], promotes active interaction and participation of students, providing evidence of the role as a companion that the professor must play in education mediated by the ICT.…”
Section: Discussionmentioning
confidence: 82%
“…However, [27] found that during the pandemic, the virtualization of teaching was perceived as having a low quality, precisely due to the lack of interaction between students and teachers, given the dependency created in the physical classroom. At the same time, it challenged the teachers with a greater role as a tutor and companion [28].…”
mentioning
confidence: 99%
“…Contudo, muito há ainda a fazer para utilizar as tecnologias da informação para fins pedagógicos inclusivos (para melhorar o ensino e a aprendizagem) e para acompanhar estudantes de diversos grupos demográficos (Vargas e Rondero, 2021). (Vargas e Rondero, 2020).. A educação virtual como educação do século XXI baseia-se nos seguintes princípios: auto-educação, auto-formação, desterritorialização, descentralização, virtualização, tecnologização e sociabilidade virtual. (Barak, 2017).…”
Section: Abstratounclassified
“…Además Aguilar & Otuyemi (2020) afirman: Los "entornos virtuales" también son definidos como recursos que complementan la gestión y la labor docente, dado que mejoran los procesos de enseñanza-aprendizaje y establecen la generación de actividades formativas orientadas a la adquisición de nuevos conocimientos y a la apropiación de los contenidos las herramientas virtuales pueden ser precisados como medios que complementan y apoyan el trabajo docente, ya que esta mejora y favorece el proceso de enseñanza -aprendizaje, además implanta actividades de formación con el objetivo de adquirir nuevos conocimientos (p.66).…”
Section: Entornos Virtualesunclassified